The Effect of Training Using Fins and Paddles on Increasing 50-Meter Freestyle (Crawl) Swimming Speed in Youth Tiss Silampari Athletes - Adika Fatahilah; Syabawaihi Syabawaihi; Ikhfa Al-Qowiyu (EDUJAVARE: International Journal of Educational Research, 2026)
This study aimed to determine the effect of training using fins, paddles, and a combination of the two on improving 50-meter freestyle (crawl) swimming speed in youth athletes at TISS (Tirta Intan Swimming School) Silampari. The study employed a quantitative method with a quasi-experimental pretest-posttest multiple group design. The sample consisted of 45 youth athletes divided into three treatment groups: a fin training group, a paddle training group, and a fin and paddle combination group, each with 15 athletes. The treatment was administered for 6 weeks, with training frequency three times per week. The research instrument used a 50-meter freestyle swimming speed test. Data were analyzed using the Shapiro-Wilk normality test, the F-max homogeneity test, the paired t-test, and one-way ANOVA. The results showed that all training methods improved 50-meter freestyle swimming speed performance. The fins group experienced an average increase of 0.68 seconds, the paddles group 0.73 seconds, and the fins and paddles combination group 0.91 seconds. Statistical test results indicate that training using both fins and paddles significantly increased swimming speed. However, a one-way ANOVA test showed no significant difference in effectiveness between the three training methods, with an F-value of 0.83, lower than the F-value of 3.22 at the 0.05 level of significance. The study concluded that training using fins, paddles, and a combination of the two were equally effective in increasing 50-meter freestyle swimming speed in TISS Silampari youth athletes, although there was no statistically significant difference in effectiveness between the training methods.